Pengaruh Related Party Transaction, Sales Growth Dan Transfer Pricing Terhadap Tax Avoidance - Dea Ananda Br Ginting; Ferdiansyah (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This study aims to analyze and test to find out about the influence of related party transaction, sales growth and transfer pricing on tax avoidance. The population used in this study is all companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange in 2019-2024. The sampling procedures used in this study are 6 (six) companies that meet the criteria for selecting data samples. The data analysis method used is the panel data regression analysis method with the help of the Eviews 12 program. The results of the study show that the best model is the Fixed Effect Model (FEM). The results of this study show that partially sales growth and transfer pricing have an effect on tax avoidance and related party transaction have no effect on tax avoidance. Meanwhile, it is simultaneously shown that related party transaction, sales growth and transfer pricing have an influence on tax avoidance.